Mesoporous organosilica nanoparticles: Degradation strategies and application in tumor therapy. Issue 5 (4th May 2021) - Guan, Lei; Chen, Jiajie; Tian, Zhengfang; Zhu, Min; Bian, Yuhai; Zhu, Yufang
Abstract: Biodegradation is a crucial issue for silica‐based mesoporous nanoparticles that is related to the biosafety in tumor therapy. Nowadays, mesoporous silica nanoparticles (MSNs) have been intensively developed to construct multifunctional nanosystems for tumor therapy due to their biocompatibility, high drug loading capacity and easy functionalization; however, their biodegradation is relatively slow and still under debate. To improve the biodegradability of silica‐based mesoporous nanoparticles, a simple organic‐inorganic hybridization strategy to synthesize mesoporous organosilica nanoparticles (MONs) has been successfully developed. By hybridizing the silica framework (–Si–O–Si–) with stimuli‐sensitive organic moieties to form organic‐inorganic network (–Si–R–Si–, R: organic moiety), when exposed to the stimuli environment, the breakdown of the organic‐inorganic network could accelerate the degradation of MONs, which is great promising for MONs as a multifunctional therapeutic nanoplatform in tumor therapy. This review aims to summarize the degradation strategies for MONs to improve biodegradability in recent years, and highlight the potential applications of MONs in tumor therapy. Finally, we also discuss the challenges of MONs for tumor therapy in future clinical translation. Abstract : The strategy of organic‐inorganic hybridization is proposed to synthesize biodegradable mesoporous organosilica nanoparticles (MONs) with potential biosafety for tumor therapy. This review summarizes the degradation strategies for MONs to improve biodegradability in recent years, and highlight the potential applications of MONs in tumor therapy. The challenges of MONs for tumor therapy in future clinical translation are also discussed.